Proceedings of the 2014 ACM/IEEE International Conference on Human-Robot Interaction 2014
DOI: 10.1145/2559636.2559676
|View full text |Cite
|
Sign up to set email alerts
|

Culturally variable preferences for robot design and use in South Korea, Turkey, and the United States

Abstract: Based on the results of an online survey conducted with participants in South Korea (N=73), Turkey (N=46), and the United States (N=99), we show that people's perceptions and preferences regarding acceptable designs and uses for robots are culturally variable on a number of dimensions, including general attitudes towards robots, preferences for robot form, interactivity, intelligence, and sociality. We also explore correlations between these design and use characteristics and factors cited as having an effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(54 citation statements)
references
References 19 publications
1
53
0
Order By: Relevance
“…It is possible that humanlike robots that outperform humans could be more accepted in some cultures than others. Past research has shown that culture determines preferences toward androids (Bartneck, 2008;Haring et al, 2014;Lee & Sabanović, 2014), and it is possible that the observed effect in our study would be even stronger with participants from cultures that have unfavorable attitudes toward androids in the first place. Arguably, robots have the potential to revolutionize the way humans go about their daily business, but ultimately, this is only possible through careful consideration of how to implement such a radical change in society.…”
Section: Limitations and Future Workmentioning
confidence: 62%
“…It is possible that humanlike robots that outperform humans could be more accepted in some cultures than others. Past research has shown that culture determines preferences toward androids (Bartneck, 2008;Haring et al, 2014;Lee & Sabanović, 2014), and it is possible that the observed effect in our study would be even stronger with participants from cultures that have unfavorable attitudes toward androids in the first place. Arguably, robots have the potential to revolutionize the way humans go about their daily business, but ultimately, this is only possible through careful consideration of how to implement such a radical change in society.…”
Section: Limitations and Future Workmentioning
confidence: 62%
“…Another issue may be linked to "public engagement-communication, consultation, and participation," which also refers to "transdisciplinary discussion in unwanted societal changes as well as a shift in science from analog to digital modeling and structure." Obviously, following a meritocratic system for deliberations, the roles and decisions of virtuous and capable leaders play a much larger role than in Western societies [137,139,140]. Thus, the role of academia in (transdisciplinary) practice-science dialogues in Japan may be more important than in Western countries.…”
Section: Appendix B2 Specific Unseens Identified By the Japanese Ertmentioning
confidence: 99%
“…First of all, the studies were performed in Turkey, with Turkish children only. As Lee et al [9] indicated, there may be cultural differences in how people imagine social robots, so it is possible that our findings are only representative for Turkish children. However, the drawings on which the elements of the toolkit were based came from Portuguese children and international Interaction Design students.…”
Section: Limitationsmentioning
confidence: 95%